Analisis Pemecahan Masalah Matematis pada Siswa yang Bergaya Kognitif Impulsif di SMP Plus An-Nuur - Wahyuni, Aliya Siti; Indriani, Evi; Islamiati, Himatul; Oktavia, Puja; Faturohman, Ikhsan (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to identify the characteristics of mathematical problem solving in students with impulsive cognitive styles. The method used in this study is a descriptive qualitative approach. The sampling technique was carried out purposively on 26 eighth-grade students of SMP Plus An-Nuur Tasikmalaya, who were selected because they were in accordance with the research criteria and were relevant to the Pythagorean Theorem material taught at that level. The main instrument used was the Matching Familiar Figures Test (MFFT) to identify students with impulsive cognitive styles. They were then given mathematical problem-solving questions related to the Pythagorean material and supplemented with interviews with the selected sample. The results of this study indicate that students with impulsive cognitive styles tend to work on problems quickly without going through the stages of understanding the problem in depth and rarely evaluate the results of the solution. Their thinking process is more focused on implementing the solution steps directly without designing strategies and reviewing the final results